Teaching practices and equitable learning in children's language education - Giannikas, Christina Nicole (Information Science Reference, 2021)
"The edited volume is a collection of research chapters that provide insights in the field of teaching English to children in pre-primary, primary and secondary education, supporting the needs of young learners of any context and background through relevant studies that include sound pedagogical and content knowledge "--